The relationship between emotional intelligence and job performance among information professionals - Yusof @ Mohd Nor, Norafiqa Shireen; Abd Kadir, Irwan Kamaruddin; Zakaria, Norizan; Kamarulzaman, Mohd Ridwan; Mohd Yunus, Alwi (Faculty of Information Management, 2025)
This article explored the relationship between Emotional Intelligence (EI) and Job Performance among Information Professionals in a selected organization in Malaysia. This study aimed to measure the level of EI among information professionals in public sectors and to determine the relationship between EI and job performance. This study employed a quantitative research method and has been participated in by 105 respondents working in the National Registration Department (NRD). A convenience sampling method was employed to obtain data analyzed using Smart PLS. This study showed that emotional intelligence improves job performance in NRD for information professionals. The study found a significant positive relationship between EI dimensions such as social awareness and job performance, while self-awareness and self-management were not significantly related. Practical implications, study limitations, and future research directions were also discussed.